Analysis of the Impact of U.S. Trade Policy Uncertainty on China Based on Bayesian VAR Model. (24th March 2022) - Yan, Huan; Xiao, Weiguo; Deng, Qi; Xiong, Sisi
Abstract : Using a set of Chinese economic data and a Bayesian vector autoregression (BVAR) model, this study empirically analyzes the spillover effects of U.S. trade policy uncertainty on the output, consumption, investment, and net export in China. The results find that U.S. trade policy uncertainty is an important factor influencing China's real economy. Specifically, an increase in U.S. trade policy uncertainty has a significant negative effect on China's output, consumption, and net export in the short and long run, but it will have a negative impact on investment in the short run and a positive impact in the medium and long run.